2004
DOI: 10.1023/b:plso.0000035539.58054.e1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between selenium and iodine uptake by spinach (Spinacia oleracea L.) in solution culture

Abstract: Interactions between Se (as selenate) and I (as iodate) uptake by spinach plants (Spinacia oleracea L.) were studied under controlled conditions using solution culture. Spinach readily accumulated both Se and I in the edible parts, the leaves, with solution-to-leaf transfer factors ranging from 3.5 to 13.4. The distribution coefficients between leaves and roots ranged from 4.07 to 5.66 for I and 4.51 to 8.59 for Se. Selenium concentrations in plant tissues were unaffected by addition of I to the nutrient solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…Plants accumulate more Se in shoot than in root tissues, but there are exceptions as well (Zayed et al 1998). It has been shown that spinach, tea plants, and ryegrass accumulate Se in leaves (Zhu et al 2004;Hu et al 2003;Cartes et al 2005). These findings do not correlate with the results presented in the current paper, where Se content in shoots is higher than in roots only after long-term (45 days) Se exposure.…”
Section: Discussioncontrasting
confidence: 97%
“…Plants accumulate more Se in shoot than in root tissues, but there are exceptions as well (Zayed et al 1998). It has been shown that spinach, tea plants, and ryegrass accumulate Se in leaves (Zhu et al 2004;Hu et al 2003;Cartes et al 2005). These findings do not correlate with the results presented in the current paper, where Se content in shoots is higher than in roots only after long-term (45 days) Se exposure.…”
Section: Discussioncontrasting
confidence: 97%
“…High dosages of Se may be toxic to plants and compete with some essential elements, such as phosphorus (P) (Broyer et al 1972;Hopper and Parker 1999;Khattak et al 1991) and sulphur (S) (Hopper and Parker 1999;White et al 2004), resulting in the deficiency of these two elements in plants. On the contrary, supplementation of Se did not significantly affect the uptake of iodine (I) (Zhu et al 2004) and molybdenum (Mo) (Khattak et al 1991).…”
mentioning
confidence: 92%
“…However, it has been evidenced that Se has many positive effects on plants, capable of accumulating this element (Golob et al 2016). Recently there were some reports about combined effects of Se and I on plants (Zhu et al 2004, Smoleń et al 2014, 2016, Germ et al 2015, Osmić et al 2017, Jerše et al 2017. However, according to our knowledge, the effect of Se and I on buckwheat grain has not been studied.…”
Section: Vsebnost Fagopirina In Rutina V Semenih Navadne Ajde Tretiramentioning
confidence: 95%